Design and Build an IoT Based Prepaid Water Usage Monitoring System and Telegram Notifications - Agus Priyanto; Sabar Setiawidayat; Faqih Rofii (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2021)
In the boarding house the use of water for each person is different for each occupant of theboarding house. The increase in water use is not proportional to the increase in water capacity and theequalization of payments for each boarding house is different. Utilization of technology Internet ofThings (IoT) and the freechat application Telegram in the application to monitor water usageinformation for each boarding house occupant. In this study, a water monitoring device was made tomonitor information from two different platforms. The server can monitor water usage information forall residents of the boarding house. Telegram provides notification information when the water capacityof boarding houses is approaching empty from each device. Using Arduino and ESP8266 as controllersand wifi connection with the server. With this system, it is easier for the boarding house owner tomonitor the water usage of each boarding house occupant.